113 Development of T cell-based immunotherapies to target dormant disseminated breast cancer cells. (9th November 2020) - Goddard, Erica; Srivastava, Shivani; Riddell, Stanley; Ghajar, Cyrus
Abstract : Background: A significant fraction of breast cancer survivors develop metastases years or even decades after initial diagnosis. 1–3 Mounting evidence suggests these late recurrences arise from dormant disseminated tumor cells (DTCs). 4–6 However, no therapy currently exists for targeting DTCs for the purpose of metastasis prevention. Immunotherapy represents a promising avenue to target dormant DTCs. Yet, a functional relationship between adaptive immunity and dormant DTCs has not been established. Methods: Here, we have utilized a bone marrow organotypic microvascular niche co-culture model and immunocompetent murine models of breast cancer dormancy to study the relationship between the adaptive immune response and dormant DTCs and to develop immunotherapies for the purpose of eliminating dormant DTCs and preventing breast cancer metastasis. Results: Our data suggest that breast cancer cells downregulate MHC class I antigen presentation upon dormancy induction, identifying one mechanism of immune evasion. Strikingly, outgrowing metastases re-express MHC I and presumably upregulate antigen presentation. These data suggest that MHC-dependent T cell-based immunotherapies may not effectively kill dormant DTCs, but that MHC-independent chimeric antigen receptor (CAR) T cells may be more applicable. Using the organotypic bone marrow microvascular niche co-culture system, we have shown that CAR T cells kill both proliferating and dormant tumor cells independent of tumor cell localization in the niche and independent of tumor cell cycle status. Further, we have established preclinical immunocompetent murine models of breast cancer dormancy to compare efficacy of engineered T cell receptor (TCR) and CAR T cells in eliminating dormant DTCs. From these models of breast cancer dormancy, we have found that CAR T cells eliminate both overt metastases and DTCs in the lung and bone marrow of mice. In contrast, preliminary data suggest that TCR T cells clear overt metastases but are less effective in clearing dormant disease, lending support that MHC I downregulation during dormancy may impact the efficacy of various T cell-based immunotherapies. Conclusions: Our findings identify CAR T cells as one potential immunotherapy to eradicate dormant disease, while simultaneously identifying both CAR and TCR T cells as effective treatments for the clearance of overt metastases. In sum, our findings lay the groundwork for developing adoptive cell therapies to eliminate dormant disease and prevent death from breast cancer metastasis. References: Pan H, Gray R, et al. 20-Year Risks of Breast-Cancer Recurrence after Stopping Endocrine Therapy at 5 Years. N Engl J Med 2017;377, 1836–1846. Karrison T, Ferguson D, Meier P. Dormancy of mammary carcinoma after mastectomy. J Natl Cancer Inst . 1999;91, 80–85. Goss PE, & Chambers AF. Does tumour dormancy offer a therapeutic target? Nat Rev Cancer 2010;10, 871–877. Aguirre-Ghiso JA. Models, mechanisms and clinical evidence for cancer dormancy. Nat Rev Cancer 2007;7, 834–846. Klein CA. Framework models of tumor dormancy from patient-derived observations. Curr Opin Genet Dev 2011;21, 42–49. Demicheli R, Abbattista A, Miceli R, Valagussa P, & Bonadonna G. Time distribution of the recurrence risk for breast cancer patients undergoing mastectomy: further support about the concept of tumor dormancy. Breast Cancer Res Treat 1996;41, 177–185.